COVID-19 pandemic: Challenges and a way forward - Panu Poutvaara; Madhinee Valeyatheepillay (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
The COVID-19 pandemic has claimed more than 1.5 million lives globally, and resulted in the worst global recession since the Second World War. This policy report provides an overview of the number of cases, death toll, and economic disruption that COVID-19 has caused, as well as of the measures taken to combat it. Our main conclusion is that suppression is the preferred option both for health and the economy. Countries that fail to suppress the pandemic risk a disastrous overburdening of their health care system, resulting in a situation in which intensive care units run out of beds and patients who could have been otherwise saved die. Sacrificing lives does not save the economy. Short of an effective vaccine, no single measure is enough to stop the pandemic. Instead, societies need a combination of effective social distancing measures, careful hygiene, use of masks in indoor public spaces, as well as contact tracing. Also, population-scale testing could play an important role in combatting this and future pandemics. Recent research has also established that public attention to COVID-19 pandemic plays an important role in explaining cross-country differences in the implementation of non-pharmaceutical interventions that save lives.
Keywords: 330; COVID-19; pandemics; suppression; non-pharmaceutical interventions; testing